2003
DOI: 10.3141/1834-04
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Early-Age Stress Development and Cracking in Low Water-to-Cement Concrete: Restrained-Ring Test with Acoustic Emission

Abstract: Early-age cracking has been found to occur in some concrete bridge decks, slabs, and pavements when the volumetric changes associated with drying, hydration, and temperature reduction are prevented. While free-shrinkage tests can quantify length change, they may not always be sufficient for detecting materials that are prone to cracking, since the potential for cracking is influenced by complex interactions of strength gain, stiffness development, creep, shrinkage, the degree of restraint, and toughness. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…The specimen was then placed in a constant RH (50%) and temperature (21 o C) room to allow drying from top and bottom surfaces of the rings. By permitting drying from only the top and bottom surfaces of the ring, moisture is lost uniformly along the radial dimension thereby simplifying modeling and providing uniform moisture loss along the radial dimension of the specimen (Weiss et al 1998;Hossain et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The specimen was then placed in a constant RH (50%) and temperature (21 o C) room to allow drying from top and bottom surfaces of the rings. By permitting drying from only the top and bottom surfaces of the ring, moisture is lost uniformly along the radial dimension thereby simplifying modeling and providing uniform moisture loss along the radial dimension of the specimen (Weiss et al 1998;Hossain et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The role of free shrinkage e SH t ð Þ ð Þ associated to autogenous, thermal and drying shrinkage which, under a mechanical restraint conditions, are responsible for the stress and strain behavior of cementitious materials has been studied experimentally in detail by many scholars (Dean, Moon, Rajabipour, Pease, & Weiss, 2006;Hossain, Pease, & Weiss, 2003;Hossain & Weiss, 2006;Moon, 2006;Moon, Couch, & Weiss, 2006;Moon, Rajabipour, & Weiss, 2004;Weiss, 1999;Weiss & Shah, 2002). Thermal strains are also included in e SH t ð Þ since the temperature of the samples were not controlled during the tests.…”
Section: Free Shrinkagementioning
confidence: 99%
“…In passive acoustic measurement, these waves are measured at the material surface and recorded. It should be noted that all acoustic events are not the same and waveform analysis can be used to differentiate between different stages of cracking such as micro-cracking, coalescence, and discrete cracking in the materials (Ohtsu et al 1991;Ouyang et al 1991;Ohtsu et al 1998;Ohtsu 1999;Hossain et al 2003;Kim and Weiss 2003;Puri and Weiss 2003;. Previous research has shown that micro-cracking progresses gradually with a series of low energy release events before a visible crack occurs in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic emission (AE) has been used by researchers to quantify the extent of the damage and capture the time of cracking in the restrained ring specimens (Hossain et al 2003;Shah 2004;Shah and Weiss 2006). Cracking and permanent deformation of materials result in the release of strain energy which leads to elastic stress wave propagation (Scott 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation